The Insider: Impact of the Gut Microbiota on Cancer Immunity and Response to Therapies in Multiple Myeloma - Brevi, Arianna; Cogrossi, Laura Lucia; Lorenzoni, Marco; Mattorre, Benedetta; Bellone, Matteo (Frontiers in Immunology, 2022)
The human microbiota is a unique set of microorganisms colonizing the human body and evolving within it from the very beginning. Acting as an insider, the microbiota provides nutrients, and mutualistically interacts with the host’s immune system, thus contributing to the generation of barriers against pathogens. While a strong link has been documented between intestinal dysbiosis (i.e., disruption to the microbiota homeostasis) and diseases, the mechanisms by which commensal bacteria impact a wide spectrum of mucosal and extramucosal human disorders have only partially been deciphered. This is particularly puzzling for multiple myeloma (MM), a treatable but incurable neoplasia of plasma cells that accumulate in the bone marrow and lead to end-organ damage. Here we revise the most recent literature on data from both the bench and the bedside that show how the gut microbiota modulates cancer immunity, potentially impacting the progression of asymptomatic monoclonal gammopathy of undetermined significance (MGUS) and smoldering MM (SMM) to full blown MM. We also explore the effect of the gut microbiome on hematopoietic stem cell transplantation, chemotherapy, immunomodulating therapy and cancer immunotherapy in MM patients. Additionally, we identify the most cogent area of investigation that have the highest chance to delineate microbiota-related and pathobiology-based parameters for patient risk stratification. Lastly, we highlight microbiota-modulating strategies (i.e., diet, prebiotics, probiotics, fecal microbiota transplantation and postbiotics) that may reduce treatment-related toxicity in patients affected by MM as well as the rates of undertreatment of SMM patients.